Análise da atividade neoextrativista da mineração de ouro no estado do Amapá (2000-2020) - Rhuan Muniz Sartore Fernandes; Miguel Patrice Philippe Dhenin (Confins)
On the one hand, the withdrawal of natural resources from the subsoil has been defended as an important generator of foreign exchange and as a mechanism for economic growth. On the other hand, those responsible (environmentalists and / or affected groups) highlight their environmental and social impacts, their inability to promote local development and to generate benefits for localities and those responsible. Based on these considerations, the objective of the paper is an analysis of the impacts of the neo-extractive mining activity in the state of Amapá, particularly the extraction of gold. Therefore, the pertinent bibliography of the area is read, with the support of a database (RAISG, SIGMINE-ANM, among others). To illustrate this situation, we can base our analysis on several projects that already exist in Amapá, either in the legal sphere (mining companies) or by illegal mining (artisanal and small scale mining), as we can see in the maps generated. They highlight what already exists in legal mining (authoritative titles) and expectations (about the right to mine, which are represented by the requirements). Thus, it is observed that the socioenvironmental impacts arising from the neo-extractive activity of minerals favor the deforestation of protected areas and / or indigenous territories, particularly due to the illegal mining that crosses the borders of the state of Amapá (French Guiana and Suriname), the which makes it possible to observe that, despite the legal framework, the neo-extractive mining activity is responsible for favoring a degradation of the Amazonian biome, with the presence of land grabbing, the creation of highways, in addition to affecting the traditional mode.